2022
DOI: 10.1055/s-0042-1757156
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Organization-Wide Electronic Health Record (EHR) System Upgrade on Physicians' Daily EHR Activity Time: An EHR Log Data Study

Abstract: Objective This article assesses the impact of a health care organization's electronic health record (EHR) upgrade on providers' daily EHR activity time. Methods Daily EHR activity time (minutes/day) was acquired through EHR log data that automatically tracks user activity. Subjects were attending and resident physicians in the departments of family medicine, hospitalist medicine, and the neonatal intensive care unit working in the inpatient setting. The EHR upgrade occurred in August 2020, and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…There is a big need for a unified architecture that will support standardized interfaces for connecting different analytical engines made by different groups, allowing them to work together both in terms of meaning and process. After the passage of the Health Information Technology for Economic and Clinical Health Act in 2009, the adoption of EHRs in the United States increased rapidly, with approximately 86% of office-based physicians and 96% of non-federal hospitals using an EHR system as of 2017 [106]. Other studies also shown that developed countries such as Canada, the United Kingdom, Australia, and Denmark have made strides in the design and implementation of EHR as part of their national e-health infrastructure, though they have also struggled in their EHR mandate due to user resistance to EHR support for clinical processes, provider burnout, decreased satisfaction [106], [107], [108], [109], and EHR interoperability with other e-health systems [105].…”
Section: B Issues Challenges and Recommendationsmentioning
confidence: 99%
“…There is a big need for a unified architecture that will support standardized interfaces for connecting different analytical engines made by different groups, allowing them to work together both in terms of meaning and process. After the passage of the Health Information Technology for Economic and Clinical Health Act in 2009, the adoption of EHRs in the United States increased rapidly, with approximately 86% of office-based physicians and 96% of non-federal hospitals using an EHR system as of 2017 [106]. Other studies also shown that developed countries such as Canada, the United Kingdom, Australia, and Denmark have made strides in the design and implementation of EHR as part of their national e-health infrastructure, though they have also struggled in their EHR mandate due to user resistance to EHR support for clinical processes, provider burnout, decreased satisfaction [106], [107], [108], [109], and EHR interoperability with other e-health systems [105].…”
Section: B Issues Challenges and Recommendationsmentioning
confidence: 99%